2019
DOI: 10.1073/pnas.1815723116
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cultural tightness and its links to innovation, urbanization, and happiness across 31 provinces in China

Abstract: We conduct a 3-y study involving 11,662 respondents to map cultural tightness—the degree to which a society is characterized by rules and norms and the extent to which people are punished or sanctioned when they deviate from these rules and norms—across 31 provinces in China. Consistent with prior research, we find that culturally tight provinces are associated with increased governmental control, constraints in daily life, religious practices, and exposure to threats. Departing from previous findings that tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
200
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(227 citation statements)
references
References 23 publications
12
200
0
1
Order By: Relevance
“…To measure norm tightness around China, we draw on a recent study in PNAS ( 2 ). In the study, researchers mapped out regional differences by surveying 11,662 people across China.…”
Section: Norm Tightness In Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…To measure norm tightness around China, we draw on a recent study in PNAS ( 2 ). In the study, researchers mapped out regional differences by surveying 11,662 people across China.…”
Section: Norm Tightness In Chinamentioning
confidence: 99%
“…Tight norms seem to have consequences for people’s psychology. For example, people in societies with tight norms are better at self-monitoring, but also less creative ( 1 3 ). Here, we look not at the consequences of tight norms, but, rather, the question of where these norms come from.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Across the Pacific Ocean, in a more recent work, Chua et al (2019) mapped cultural tightness and looseness across 31 provinces in China, and revealed its relations to important regional indicators. They found that provincial tightness is positively associated with governmental control, religious practices, and restrictions in daily life.…”
Section: Geographic Level Correlates Of Cultural Tightness-loosenessmentioning
confidence: 99%
“…This was in accordance with the literature that even tight societies allowed some deviant behaviors. For example, excessive drinking was randomly criticized in Japan (Gelfand & Harrington, 2015), and tight provinces in China had a high tolerance of LGBT (lesbian, gay, bisexual and transgender) community (Chua, Huang, & Jin, 2019). Meanwhile, the gap between the strength of normative influence on different behaviors came from the motive to relate socially to others.…”
Section: Behaviorsmentioning
confidence: 99%